The role of liver transplantation in the care of primary hepatic vascular tumours in children - Grimaldi, Chiara; de Ville de Goyet, Jean; Bici, Kejd; Cianci, Maria Chiara; Callea, Francesco; Morabito, Antonino (Frontiers in Oncology, 2022)
Liver transplantation (LT) is the standard of care for many liver conditions such as end-stage liver diseases, inherited metabolic disorders, and primary liver malignancies. In the latter group, indications of LT for hepatoblastoma and hepatocellular carcinoma evolved and are nowadays available for many non-resectable cases, though selection criteria apply, as the absence of active metastases. Evidence of good long-term outcomes has validated the LT approach for the management of these malignancies in the context of specialist and multidisciplinary approach. Nevertheless, the role of LT in the treatment of primary vascular tumors of the liver in children, both benign and malignant, remains somewhat controversial. The rarity of the different diseases and the heterogeneity of pathological definitions contribute to the controversy and making the evaluation of benefit/risk ratio and of the outcomes quite difficult. In this narrative review we give an overview of primary vascular tumors of the liver in children, the possible indications and the outcomes of LT.